2020
DOI: 10.5812/aapm.104151
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Management of Il-6 Driven Cytokine Storm Related to COVID-19 in a Patient with Recent Spinal Cord Stimulator Implants: A Case Report

Abstract: Introduction: In the last months of 2019, the advent of a new virus called SARS-CoV-2 caused the spread of a pandemic disease, COVID-19, that has afflicted patients with chronic pain. Case Presentation: We describe a COVID-19 patient recently implanted with a spinal cord stimulator for FBSS, treated with Tocilizumab for cytokine storm complicating SARS-COV-2 infection. This patient developed a delayed hyperimmune reaction, causing an inflammatory reaction in the surgical pocket site, well treated with total re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
0
6
1
Order By: Relevance
“…Previous studies reported a wide range of mortality rates among critically ill patients admitted to ICU, from 16% to 38%, 62%, 67%, and 80% (12)(13)(14)(15)(22)(23)(24). In our study, overall outcomes were poor in severe patients who received ICU care, and the mortality rate (84.6%) was considerably higher than other studies.…”
Section: Discussioncontrasting
confidence: 60%
“…Previous studies reported a wide range of mortality rates among critically ill patients admitted to ICU, from 16% to 38%, 62%, 67%, and 80% (12)(13)(14)(15)(22)(23)(24). In our study, overall outcomes were poor in severe patients who received ICU care, and the mortality rate (84.6%) was considerably higher than other studies.…”
Section: Discussioncontrasting
confidence: 60%
“…A high IL-6 level is associated with postoperative complications and is recognized as a predictor of morbidity after surgical interventions ( 6 , 7 ). Inhibition of the production of cytokines, including IL-6, can protect the body against traumatic injuries and infections under pathological conditions; therefore, cytokine inhibitors or antagonists may have the capacity to reduce tissue/organ dysfunction ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…The distance between patients during recovery should be at least six feet. The number of the medical crew should be kept minimum, and, if possible, the procedure should be conducted in a negative pressure room (16,17).…”
Section: Discussionmentioning
confidence: 99%